Inter-faith conflict mediation mechanisms and peacebuilding in Nigeria (2014)
Religious conflicts have been prevalent in Nigeria in the last couple of decades. Currently, the country is experiencing a scourge of violent Islamic fundamentalism which is threatening its cohesion. Several violent religious conflicts in different parts of the country have pushed citizens to, sometimes, query the modalities of the very existence of the country within the context of the uneasy co-habitation of diverse people of over 250 cultures - in a country which had hitherto witnessed harmonious inter-cultural relationships for over a century. Several strategies, ranging from policy instruments, national dialogues (one was concluded in 2014), compulsory national youth service, civil and communal initiatives have been evolved to manage ethno-religious relationship among the diverse groups, but these seem to have failed in stopping religious conflicts in certain parts of Nigeria. Inter-faith mechanisms, which involve deliberate facilitation and management of interaction among the leaders and followers of dominant religious groups at the national, state and community levels have, therefore, been adopted by governments and community based organisations to directly address religious frictions and prevent such frictions from degenerating into violence. Inter-faith dialogues, education and enlightenments remain major features of inter-faith mediation, but these are also combined with the economic capacity building of religious adherents to distract them from the frustrations pushing them into religious violence. This paper aims at reviewing some of the interfaith peacebuilding efforts for reducing and managing religious conflicts in Nigeria and assessing how these efforts have been facilitating peaceful relationships among diverse religious groups in the country. Consequently, the paper will suggest ways of strengthening and improving such mechanisms to curtail the dangerous trend of Islamic radicalisation and proliferation of terrorism activities making the Northeastern part of the country ungovernable and spawning distrust, insecurity and uncertainty for the people